2009
DOI: 10.1177/0042098009351186
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility and Cognition: The Effect of Transport Mode on Spatial Knowledge

Abstract: Spatial behaviour and decision-making require knowledge of the urban environment, including opportunities available and the means to reach them. Thus, variations in spatial knowledge can result in radically different levels of effective accessibility, despite similar locations, demographics and other factors commonly thought to influence travel behaviour. Cognitive maps, which develop primarily through wayfinding and travel experience, are individuals' repositories of spatial knowledge. This paper examines whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 26 publications
2
51
0
1
Order By: Relevance
“…walking, riding a bicycle or driving a car) and passive modes (e.g. taking a bus, train, or being driven in a car).These modes can affect learning and the refinement of individuals' cognitive maps (Mondschein et al, 2009). It is hypothesized that cycling and walking generate more complete cognitive maps since, in active transport modes; people have direct interaction with their environment which aids the development of a more complete cognitive map.…”
Section: Navigation Systems and Gpsmentioning
confidence: 99%
See 1 more Smart Citation
“…walking, riding a bicycle or driving a car) and passive modes (e.g. taking a bus, train, or being driven in a car).These modes can affect learning and the refinement of individuals' cognitive maps (Mondschein et al, 2009). It is hypothesized that cycling and walking generate more complete cognitive maps since, in active transport modes; people have direct interaction with their environment which aids the development of a more complete cognitive map.…”
Section: Navigation Systems and Gpsmentioning
confidence: 99%
“…Different modes of transport can have different effects on cognitive maps, for instance, a study by Hart in 1981 found that, amongst school children, 'active' travel modes including cycling and walking were stronger contributors to the development of their spatial knowledge than passive modes, for instance being passengers in a car or a school bus (Mondschein et al, 2009).…”
Section: Theory Calculation and Analysismentioning
confidence: 99%
“…Both types of attributes do not necessarily coincide and therefore may relate differently with physical activity behavior. For example, while objective availability of pertinent destinations in a neighborhood may be high, a person’s perceived availability can be low due to the fact that a person may not be aware of all feasible destinations in her/his neighborhood [21,22]. A decreased environmental awareness may in turn lead to a lower propensity to walk in that neighborhood, although the objective availability of destinations suggests otherwise.…”
Section: Introductionmentioning
confidence: 99%
“…Way-finding ability. The way-finding ability of visitors is very important in terms of accessibility to resources such as tourist attractions and shopping centres (Dogu & Erkip, 2000;Kwan, 1999;Mondschein, Blumenberg, & Taylor, 2008;Walmsley & Jenkins, 1992). Way-finding has two major components: decision making and physical movement.…”
Section: Spatial Abilitiesmentioning
confidence: 99%